Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702214
|View full text |Cite
|
Sign up to set email alerts
|

User-Defined Game Input for Smart Glasses in Public Space

Abstract: Smart glasses, such as Google Glass, provide alwaysavailable displays not offered by console and mobile gaming devices, and could potentially offer a pervasive gaming experience. However, research on input for games on smart glasses has been constrained by the available sensors to date. To help inform design directions, this paper explores userdefined game input for smart glasses beyond the capabilities of current sensors, and focuses on the interaction in public settings. We conducted a user-defined input stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…Possible solutions include the application of the accelerometer [22], smart fabrics [23], or eye-tracker [24]. Other methods and comparison study were presented in [25]. In this study we verified the fundamental interaction procedure using the eyetracker, which is a part of the eGlasses platform.…”
Section: System Architecture and Proposed Interaction Methodsmentioning
confidence: 85%
“…Possible solutions include the application of the accelerometer [22], smart fabrics [23], or eye-tracker [24]. Other methods and comparison study were presented in [25]. In this study we verified the fundamental interaction procedure using the eyetracker, which is a part of the eGlasses platform.…”
Section: System Architecture and Proposed Interaction Methodsmentioning
confidence: 85%
“…One such example is the transition between touch and mid-air interaction. While recent research has shown that for some tasks (e.g., gaming) users would prefer mid-air input for smartglasses [96], there are clearly benefits of haptic qualities of surfaces [97], which are evident in touch being the dominant interaction mode for smartphones and smartwatches. While researchers have begun to investigate the joint interaction space of touch and free-space input (e.g., [42,43,98]), there is clearly a larger design space to explore in highly mobile multi-device scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers [26,[37][38][39][40] proposed a new "1-to-3" experimental protocol for gesture elicitation, in which participants were required to derive three gesture candidates for each target task. They speculated that such a method may prompt end-users to think more deeply about which gestures were most appropriate for specified tasks, rather than directly using those legacy-inspired gestures popped out of their minds easily.…”
Section: Gesture Elicitation Studymentioning
confidence: 99%